Pengaruh Berbagai Tipe Flipped Classroom Berbantuan Learning Management System (LMS) terhadap Kemampuan Berpikir Kreatif pada Siswa SMP - Azmi Fathin Eka Nugraha; Adnan; Firdaus Daud (Postgraduate, University of Mataram, 2025)
This study aims to analyze the effect of various types of flipped classrooms (Mastery Flipped, Peer Instruction Flipped, and Problem-Based Learning Flipped) assisted by Learning Management System (LMS) on creative thinking skills. The research design used is pretest-posttest control group design. The type of research is experimental. The research population came from grade VII students of SMP Negeri 17 Baubau consisting of 5 classes. The research sample consisted of 104 students consisting of 4 classes. The type of instrument used was a creative thinking ability test which aims to assess the impact of the implementation of flipped classrooms on students' creative thinking skills. The test was given before and after the implementation of flipped classrooms. The data collection technique used was simple random sampling. The data analysis used was descriptive and inferential data analysis, namely by conducting normality, homogeneity, ANCOVA, and LSD tests. The results showed that the three types of flipped classrooms had a significant effect on improving creative thinking skills, with the PBL-Flipped type showing the highest average score. Problem-based discussions in PBL-Flipped train students to see problems from various perspectives, generate unique solutions, and improve analytical and innovative skills. In addition, the use of LMS strengthens the effectiveness of the flipped classroom by providing flexible access to materials, increasing interaction between teachers and students, and creating a more personal and dynamic learning environment.